Bulgaria 2019 - Republic of Bulgaria. National Statistical Institute (Sofia: National Statistical Institute)
The National Statistical Institute presents the bilingual (Bulgarian/English) brochure Bulgaria 2019 to users of statistical information. The brochure is addressed to a wide range of users (international institutions, business, students, experts etc.) and changes the traditional presentation of statistical information by offering an innovative structure with a parallel translation in English. The publication contains topical statistical information about the demographic, social and economic development of the country.
Republic of Bulgaria -- Geographic location and climate -- Population -- Household income, expenditure and consumption -- Labour force -- Education -- Research and development activity -- Culture and arts -- Health -- Tourism -- Justice -- Environment -- National accounts -- Exports and imports of goods -- Finance and credits -- Consumer prices -- Non-financial enterprises -- Agriculture -- Forestry -- Energy -- Industry -- Investments and construction -- Transport -- Domestic trade, accommodation and food service activities -- Bulgaria in Europe in 2017
Keywords: Bulgaria; Statistics - Bulgaria; Demographic development - Bulgaria; Social and economic development - Bulgaria